Aplikasi Pemesanan Online Barbershop Berbasis Android untuk Meningkatkan Layanan - Cep Lukman Rohmat; Irfan Ali; Mulyawan Mulyawan; Tati Suprapti; Utami Aryanti (Ma'soem University, 2021)
The development of information and technology is a development that can be felt in everyday life, almost all activities already use digital. The problem in the barbershop business is the length of the queue which causes customers to feel bored or there are also busy customers. Therefore, technology is needed in the barbershop business. Based on these problems, it can be concluded that there is a need to build an android-based ordering application. The purpose of this research is to increase productivity, creativity, revenue and customer satisfaction. This study uses the stages of the Waterfall method. The Waterfall method is used as a reference in the process of making the online ordering application. The results of this study are an android-based online ordering application, this application is enough to help customers so they don't have to bother waiting in line at the barbershop because customers can set schedules on the application, especially during a pandemic like today. This application displays information about available time slots and those that have been booked by other customers so that customers can adjust their free time. The barbershop also does not need to register customers who place orders manually. This online booking application has passed trials with white box testing and black box testing methods. The result is that all the components contained in this online booking application system work as expected.